2014
DOI: 10.1039/c3ob41971a
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective N-deacetylation under mild conditions

Abstract: A mild and efficient chemoselective N-deacetylation using the Schwartz reagent at room temperature in rapid time is described. The mild and neutral conditions enable orthogonal N-deacetylation in the presence of some of the common protecting groups (viz. Boc, Fmoc, Cbz, Ts). The deprotection conditions did not induce any epimerization at the chiral amino centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
0
34
0
3
Order By: Relevance
“…The peak at ~1645 cm -1 , common to all samples, was attributed to the carbonyl group of N-octadecylamide, 24 which was formed by the nucleophilic attack of the amine group to the carbonyl group of acetylacetonate ligand ( Figure 2S). Additionally, the N-H stretching at ~3290 cm -1 and the N-H wagging mode at ~724 cm -1 of ODA are present, while they are downshifted and of reduced intensity compared to the same features of the neat ODA (~3336 cm -1 Figure 3Sa), [25][26][27] indicating that it is bound on the metal core. 28 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 verified by performing a ninhydrin colorimetric assay ( Figure 5S).…”
Section: Structural Characterizationmentioning
confidence: 91%
“…The peak at ~1645 cm -1 , common to all samples, was attributed to the carbonyl group of N-octadecylamide, 24 which was formed by the nucleophilic attack of the amine group to the carbonyl group of acetylacetonate ligand ( Figure 2S). Additionally, the N-H stretching at ~3290 cm -1 and the N-H wagging mode at ~724 cm -1 of ODA are present, while they are downshifted and of reduced intensity compared to the same features of the neat ODA (~3336 cm -1 Figure 3Sa), [25][26][27] indicating that it is bound on the metal core. 28 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 verified by performing a ninhydrin colorimetric assay ( Figure 5S).…”
Section: Structural Characterizationmentioning
confidence: 91%
“…33 In a similar manner, base labile Fmoc protected amine 7e was formed in 98% yield with 9-fluorenylmethyloxycarbonyl chloride (Fmoc-Cl) and pyridine in DCM (entry 3). 34 The acetylation of tetralone 6 was achieved using 4-dimethylaminopyridine (DMAP), acetic anhydride (Ac 2 O) in Et 3 N giving acetyl protected ketone 7f in 97% yield (entry 4). 13,35 Several cyclic olefinic substrates were synthesized via reduction/dehydration protocol.…”
Section: Resultsmentioning
confidence: 99%
“…[26,27] Twenty years later, Bhat and co-workers [44] reported a general study on N-deacylation of various N-acetamides with [Cp 2 Zr(H)Cl]. Such an approach was used in the already mentioned synthesis of paclitaxel and its analogues by chemoselective deacylation of taxanes naturally occurring in the yew tree in the mid-90s (Scheme 35).…”
Section: Reduction Of Amides and Derivativesmentioning
confidence: 99%
“…Such an approach was used in the already mentioned synthesis of paclitaxel and its analogues by chemoselective deacylation of taxanes naturally occurring in the yew tree in the mid-90s (Scheme 35). Additionally, Bhat and coworkers [44] demonstrated that the described hydrozirconation/ hydrolysis sequence can be applied successfully for chemoselective N-deacetylation of protected amino acids without any racemization (Scheme 37). Upon treatment with Schwartz's reagent (1.5-2 equiv.)…”
Section: Reduction Of Amides and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation